Generation of Zinc Oxide-Gold Textured Janus Nanowire for Bio-recognition - Rajintraprasat, HP; Nathan, TD; Hashim, U; Bosh, GSC; Perumal, V; Balakrishnan, SR; Foo, KL (Elsevier Ireland Ltd, 2024)
Indexed by WOS